Omnibus Law as an Answer to Employment Law Problems in Indonesia - Listio, Ronald (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Most people think that the Omnibus Law, the Labor Law, and/or the Job Creation Law are the same, but they are different. this study aims to analyze the Omnibus Law. The research method used in this research is a juridical qualitative method. the result of this research is that the Omnibus Law needs to be understood as a scientific method of forming laws, while the Job Creation Law is a legal product regarding employment which is the result of the Omnibus Law. Thus, the focus on reforming legislation must be on the substance of Law no. 11 of 2020 concerning Copyright and not the Omnibus Law. So, it can be concluded that there needs to be a special understanding of.